(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2013)
Islam forbids lying, dishonesty, fraud and deceit in any business transaction. Islam also provides a practical solution for both parties involved in a dispute concerning supplying goods without quality, with the provision of haqq al-khiyar (the right to have an option or choice). Based on the principle of al-khiyar, any party who is not satisfied with the quality of the goods supplied based on the contract has the right to decide whether to proceed with or cancel the contract. This article discusses the principles of haqq khiyar al-ru’yah (option to cancel upon viewing) as one of the rights under Islamic law and its harmonisation with the principle of option for non-compliance with the description/sample in the Consumer Protection Act 1999. Harmonisation approach was adopted in analysing the similarities and differences between the principle of al-khiyar in Islamic law and the principle of option in the laws of Malaysia. The findings of the research reveal that both Islamic law and Malaysian law have given buyers the right to follow the principle of khiyar al-ru’yah in a contract, when certain conditions are fulfilled. Keywords: principle of khiyar ru’yah, law of contract, Islamic law, harmonization of laws, non-compliance with the description or sample, laws of the Consumer Protection Act 1999